High and Low Levels of Employee Performance: The Role of Transformational Leadership Styles and Employee Engagement - Fitri Rezeki; Hamzah Muhammad Mardiputera; Anna Wulandari (Cita Konsultindo Research Center, 2023)
This research investigated the relationships between Work Engagement, Transformational Leadership, and Employee Performance. The analysis revealed that Work Engagement did not have a direct statistically significant impact on Employee Performance. However, Transformational Leadership was found to have a strong and significant positive effect on Employee Performance. Moreover, when considering the combined influence of Work Engagement and Transformational Leadership, a significant relationship with Employee Performance was observed. These findings suggest that organizations should prioritize the development of transformational leadership skills to enhance performance outcomes. While Work Engagement is important for employee well-being, its direct impact on performance may be limited. The study highlights the need for organizations to cultivate a work environment that promotes employee engagement and effective leadership practices. Further research is necessary to explore additional factors that may influence employee performance. These conclusions provide valuable insights for organizations aiming to improve performance and create a positive work environment.